Exploring intermittency in numerical simulations of turbulence using single and multi-spacecraft analysis - Guerrero Guio, Andres F.; Agudelo Rueda, Jeffersson A.; Vargas Domínguez, Santiago (Frontiers in Astronomy and Space Sciences, 2024)
The energy dissipation in collisionless plasmas as the solar wind is not yet fully understood.The intermittent nature of magnetic structures appears to be a fundamental part of the energy cascade. Understanding energy transfer and dissipation in the solar wind requires an accurate description of its intermittency. Upcoming multi-spacecraft missions will provide new insight on this matter. However, the use of multi-point data requires developing new data analysis techniques as well as cross-validating these techniques. In this study, we address the latter and explore the intermittency in a 3D simulation of anisotropic plasma turbulence using two approaches. We implement the standard single-spacecraft partial variance increments technique as well as a multi-point partial variance increments technique. We contrast these two techniques and explore their dependence on the angle between the spacecraft-configuration travel direction and the background magnetic field.